OPEN ACCESS REPOSITORIES IN NIGERIAN LIBRARIES: ISSUES AND CHALLENGES (NAU Journal of Library and Information Science, 2022)
This paper discussed issues and challenges involved in the management of open access repositories in Nigerian libraries. Open access repository concerns the archiving of a research report or book written into a database belonging to an institution. This platform allows free access and exchange of ideas without subscriptions. The era of publishing in closed access is gradually being phased out with the emergence of Information and Communication Technologies (ICTs). This new media form has enabled gathering together of already published works by an institution, on an institution and its staff into a database called institutional repository. Expectedly, this synergy has numerous advantages amongst which is free access and exchange of knowledge. This in turn promotes web visibility and global university ranking. This paper thus highlights software that enhances open access repositories, types of open access repositories, advantages, challenges, as well as strategies that can be adopted to enhance open access repositories in Nigerian libraries.
Keywords: Institutional Repositories; ICTs; Open access; Nigerian Libraries